Histone H3 Lysine 36 Trimethylation Is Established over the Xist Promoter by Antisense Tsix Transcription and Contributes to Repressing Xist Expression - Ohhata, Tatsuya (Mol Cell Biol, 2015)
One of the two X chromosomes in female mammals is inactivated by the noncoding Xist RNA. In mice, X chromosome inactivation (XCI) is regulated by the antisense RNA Tsix, which represses Xist on the active X chromosome. In the absence of Tsix, PRC2-mediated histone H3 lysine 27 trimethylation (H3K27me3) is established over the Xist promoter. Simultaneous disruption of Tsix and PRC2 leads to derepression of Xist and in turn silencing of the single X chromosome in male embryonic stem cells. Here, we identified histone H3 lysine 36 trimethylation (H3K36me3) as a modification that is recruited by Tsix cotranscriptionally and extends over the Xist promoter. Reduction of H3K36me3 by expression of a mutated histone H3.3 with a substitution of methionine for lysine at position 36 causes a significant derepression of Xist. Moreover, depletion of the H3K36 methylase Setd2 leads to upregulation of Xist, suggesting H3K36me3 as a modification that contributes to the mechanism of Tsix function in regulating XCI. Furthermore, we found that reduction of H3K36me3 does not facilitate an increase in H3K27me3 over the Xist promoter, indicating that additional mechanisms exist by which Tsix blocks PRC2 recruitment to the Xist promoter.